Confucianism A Very Short Introduction. - Gardner, Daniel K. (Oxford : Oxford University Press, 2014)
To understand China, it is essential to understand Confucianism. First formulated in the sixth century BCE, the teachings of Confucius would come to dominate Chinese society, politics, economics, and ethics. In this Very Short Introduction, Daniel K. Gardner explores the major philosophical ideas of the Confucian tradition, showing their profound impact on state ideology and imperial government, the civil service examination system, domestic life, and social relations over the course of twenty-six centuries. Gardner focuses on two of the Sage's most crucial philosophical problems-what makes fo.
Studies of early Confucian thoughtStudies of later Confucian thought; Education and the examination system; Confucianism and the state; Confucianism and the family; Confucianism and women; Confucianism since the twentieth century; Index
Description based upon print version of record.
Description based on print version record.
Keywords: Confucianism; PHILOSOPHY / Eastern; Electronic books